Barriers and facilitators to undertaking nutritional screening of patients: a systematic review. Issue 3 (19th January 2013) - Green, S. M.; James, E. P.
Abstract Background Recent reports have suggested that registered nurses may not screen patients admitted to their care for malnutrition. The objective of this integrative review was to locate and review published research investigating barriers and facilitators to nutritional screening by nurses. Methods A systematic search for relevant English language publications was conducted through CINAHL®, Web of Science, MEDLINE® and EMBASE and an Internet search engine (completed November 2011). Reference lists of relevant publications were also searched. Search terms included nursing, dietetics, nutrition disorders and screening, as well as associated MeSH® terms and Subject Headings. Six hundred and sixteen publications were identified and 605 were excluded. Publications reporting research concerning barriers and facilitators to nutritional screening by nurses were selected using exclusion and inclusion criteria. These were reviewed and the key findings described, categorised, combined, reviewed and refined to create themes. Results Eleven publications were reviewed. Publications primarily reported hospital‐based studies undertaken in three continents and considered barriers rather than facilitators. Five themes emerged: organisational culture, competing priorities, the value of clinical judgement, training and education, and discrepancy between attitudes and practice. Conclusions Studies primarily involved acute care and indicated that routine screening for malnutrition will not take place unless it is considered an integral part of nursing assessment that is required by policy and resourced appropriately. Qualitative studies investigating barriers and facilitators to screening for malnutrition in community settings are needed and research is required to test interventions designed to modify or remove barriers and facilitate screening.